The effects of urban logistics and destination competence on tourism: Comparative analysis of gastronomy cities of Afyonkarahisar, Hatay and Gaziantep - Kılıç, Binali; Delipınar, Gül Esin (Afyon Kocatepe Üniversitesi)
People migrate from rural areas to urban areas to have a better standard of living and education, healthcare and job opportunities. Along with trade and tourism, the high living standards of citizens are developing due to communication and transportation. The reason why gastronomy cities want to join the UNESCO Creative Cities Network is that they want to increase the living standards of the city and country residents by taking the share they want from the tourism market in the world. Therefore, logistics and destination competences are important for gastronomy cities. In the literature review, it was seen that there was no study on the relationship and effects of urban logistics and destination capabilities with gastronomy cities. For this reason, this study was conducted as a comparative research on the logistics and destination capabilities of gastronomy cities. It is seen that Afyonkarahisar ranks first in gastronomy and destination capabilities. However, It is seen that Afyonkarahisar ranks 10th in the life index of Turkey. Hatay ranks the first in the life index. Gaziantep and Afyonkarahisar, which are gastronomy cities, have the same ranking in livability. Furthermore, considering sustainability, Afyonkarahisar ranks first with the highest score. In terms of mobility, Gaziantep is the first and Afyonkarahisar ranks the second.

İnsanlar daha iyi bir yaşam standardı, eğitim, sağlık hizmetleri ve iş fırsatlarına sahip olmak için kırsal alanlardan kentsel alanlara göç ederler. Ticaret ve turizmin yanı sıra iletişim ve ulaşım sayesinde vatandaşların yüksek yaşam standartları gelişmektedir. Gastronomi şehirlerinin UNESCO Yaratıcı Şehirler Ağına katılmak istemelerinin nedeni, dünyadaki turizm pazarından istedikleri payı alarak şehir ve ülke sakinlerinin yaşam standartlarını yükseltmek istemeleridir. Bu nedenle lojistik ve destinasyon yetkinlikleri gastronomi kentleri için önemlidir. Literatür taramasında, kentsel lojistiğin ve destinasyon yeteneklerinin gastronomi kentleri ile ilişkisi ve etkileri üzerine bir çalışmaya rastlanmamıştır. Bu nedenle bu çalışmada, gastronomi şehirlerinin lojistik ve destinasyon yetenekleri üzerine karşılaştırmalı bir araştırma olarak yapılmıştır. Afyonkarahisar'ın Türkiye‟nin yaşam endeksinde 10. sırada yer aldığı görülmektedir. Yaşam endeksinde Hatay birinci sırada yer alırken, Afyonkarahisar, gastronomi ve destinasyon yeteneklerinde birinci sırada yer almaktadır. Gaziantep ve Afyonkarahisar gastronomi şehri yaşanabilirlik açısından aynı sıralamaya sahiptir. Sürdürülebilirlik açısından Afyonkarahisar gastronomi şehri en yüksek puana sahip olup ilk sırada yer almaktadır. Hareketlilik açısından Gaziantep birinci, Afyonkarahisar ikinci sıradadır.
Kentsel lojistik ve destinasyon yeteneklerin turizme etkileri: Afyonkarahisar, Hatay ve Gaziantep gastronomi şehirlerinin karşılaştırmalı analizi
Keywords: Logistic Competence; Destination Competence; Gastronomy Cities; Tourism; Lojistik Yetenekler; Destinasyon Yetenekleri; Gastronomi Şehirleri; Turizm